2009
DOI: 10.1073/pnas.0911500106
|View full text |Cite
|
Sign up to set email alerts
|

A double-hexameric MCM2-7 complex is loaded onto origin DNA during licensing of eukaryotic DNA replication

Abstract: During pre-replication complex (pre-RC) formation, origin recognition complex (ORC), Cdc6, and Cdt1 cooperatively load the 6-subunit mini chromosome maintenance (MCM2-7) complex onto DNA. Loading of MCM2-7 is a prerequisite for DNA licensing that restricts DNA replication to once per cell cycle. During S phase MCM2-7 functions as part of the replicative helicase but within the pre-RC MCM2-7 is inactive. The organization of replicative DNA helicases before and after loading onto DNA has been studied in bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
612
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 494 publications
(656 citation statements)
references
References 43 publications
(95 reference statements)
21
612
0
5
Order By: Relevance
“…What triggers the subsequent closure of the MCM2-7 ring has not been established. In origin recognition complex-dependent loading reactions, MCM2-7 particles become topologically linked to duplex DNA as double hexamers (8,9), suggesting that the initiation machinery, inter-MCM interactions, and/or nucleic acid binding may seal the Mcm2/5 gate. Biochemical studies of SceMCM2-7 have also indicated that nucleotide alone could promote ring closure (14,15); however, EM analyses of the DmeMCM2-7 complex have not detected this effect (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…What triggers the subsequent closure of the MCM2-7 ring has not been established. In origin recognition complex-dependent loading reactions, MCM2-7 particles become topologically linked to duplex DNA as double hexamers (8,9), suggesting that the initiation machinery, inter-MCM interactions, and/or nucleic acid binding may seal the Mcm2/5 gate. Biochemical studies of SceMCM2-7 have also indicated that nucleotide alone could promote ring closure (14,15); however, EM analyses of the DmeMCM2-7 complex have not detected this effect (16).…”
mentioning
confidence: 99%
“…During the G1-phase of the cell cycle, MCM2-7 heterohexamers are loaded onto DNA by the origin recognition complex together with the Cdc6 and Cdt1 proteins (8,9). As cells enter S-phase, MCM2-7 is activated through phosphorylation of Mcm2, Mcm4, and Mcm6 by the Dbf4-dependent Cdc7 kinase (10,11) and the chaperoned association of two accessory factors, Cdc45 and GINS (11).…”
mentioning
confidence: 99%
“…A lack of loaded single hexamers and the presence of multiple Cdt1/Mcm2-7 complexes before Mcm2-7 loading supports a model in which both hexamers are loaded in a concerted fashion Takara and Bell 2011). Importantly, both EM and topological linkage studies indicate that loaded Mcm2 -7 complexes encircle and slide nondirectionally on dsDNA (Evrin et al 2009;). Thus, loaded Mcm2 -7 is topologically linked to the DNA but is neither active as a helicase nor tightly engaged with the DNA.…”
Section: Structure Of Loaded Mcm2 -7mentioning
confidence: 79%
“…Unlike the archaea homologs, Mcm2 -7 double hexamers are only detected after loading. Mcm2 -7 double hexamers survive treatment with DNase and gel filtration, indicating that once formed, these complexes are very stable (Evrin et al 2009;Gambus et al 2011). Based on structural studies of the archaea Mcm complex, these interactions likely involve the Zn-finger domains in the amino termini of Mcm2 -7 subunits (Fletcher et al 2003).…”
Section: Structure Of Loaded Mcm2 -7mentioning
confidence: 99%
See 1 more Smart Citation